2022
DOI: 10.3389/fimmu.2022.810824
|View full text |Cite
|
Sign up to set email alerts
|

A Spontaneous H2-Aa Point Mutation Impairs MHC II Synthesis and CD4+ T-Cell Development in Mice

Abstract: Major histocompatibility complex class II (MHC II) is an essential immune regulatory molecule that plays an important role in antigen presentation and T-cell development. Abnormal MHC II expression can lead to immunodeficiency, clinically termed as type II bare lymphocyte syndrome (BLS), which usually results from mutations in the MHC II transactivator (CIITA) and other coactivators. Here, we present a new paradigm for MHC II deficiency in mice that involves a spontaneous point mutation on H2-Aa. A significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The results suggested that the expression of Psmb8 and H2-Aa was upregulated after treatment with 13 (Figure G,H). Psmb8 encodes a catalytic subunit of specialized immunoproteasomes, serving as a crucial component for DCs to gain higher affinity antigen presentation via MHC-I binding sites. , H2-Aa also encodes a catalytic subunit of specialized immunoproteasomes, primarily involved in the generation of MHC-II antigen presentation . Collectively, upon treatment of 13 , it has been demonstrated that the activation of various antigen presentation-related genes was enhanced, initiating downstream T cell activation and promoting increased tumor infiltration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that the expression of Psmb8 and H2-Aa was upregulated after treatment with 13 (Figure G,H). Psmb8 encodes a catalytic subunit of specialized immunoproteasomes, serving as a crucial component for DCs to gain higher affinity antigen presentation via MHC-I binding sites. , H2-Aa also encodes a catalytic subunit of specialized immunoproteasomes, primarily involved in the generation of MHC-II antigen presentation . Collectively, upon treatment of 13 , it has been demonstrated that the activation of various antigen presentation-related genes was enhanced, initiating downstream T cell activation and promoting increased tumor infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…55,56 H2-Aa also encodes a catalytic subunit of specialized immunoproteasomes, primarily involved in the generation of MHC-II antigen presentation. 57 Collectively, upon treatment of 13, it has been demonstrated that the activation of various antigen presentation-related genes was enhanced, initiating downstream T cell activation and promoting increased tumor infiltration.…”
Section: Analysis Of Thementioning
confidence: 99%
“…Major histocompatibility complex class II (MHC II) is an important immune regulatory molecule that plays an important role in both antigen presentation and immune cell development. H2-Aa, as part of the MHC class II protein complex, has been associated with a variety of diseases, including autoimmune diseases and cancers of the gastrointestinal system, and is a significant pro-inflammatory-related gene ( Zhao et al, 2022 ). Ccl5 is homologous to human CCL5 (C-C motif chemokine ligand 5), a key pro-inflammatory chemokine that induces in vitro migration and recruitment of a variety of cells, including T cells, and plays a role in a variety of biological processes including cancer and atherosclerosis.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it was demonstrated that mutant mice with ∼8-fold reduced H2-I-A expression (I-A 12% mice) possess a significantly decreased CD4 + T-cell subset, the phenotype accompanied by autoimmune-like reactivity and less efficient response against the intracellular bacterium, Listeria monocytogenes ( 3 ). Recently, a novel mutation (eight-base deletion in h2aα mRNA) resulting in an amino acid deletion in the H2-Aα molecule and significant numerical and functional reductions in the CD4 + T-cell population was identified ( 4 ). Given that a total abrogation of MHC-II expression due to either KO mutations in Class-II-encoding genes themselves, or dysfunction of key genetic regulators of their expression, lead to a well-known severe immunodeficiency called type II bare lymphocyte syndrome ( 5 , 6 ), there is no doubt that seriously impaired MHC-II expression leads to profound CD4-associated immune aberrations.…”
Section: Introductionmentioning
confidence: 99%